The prevalence of dermatological infection in outpatient dermatology clinic of RSUD Wonosari in January-September 2016 - Trijanto Agoeng Noegroho; Rosmelia .; Lamya Muthia Nabila (Faculty of Medicine, Universitas Islam Indonesia, 2017)
Background: The Skin is a complex organ that protects humans from their surrounding environment, like an infectious pathogenic agent, sunlight exposure, temperature, or other exposures. Skin infections can be divided into bacterial, viral, or fungal infections where infestations of bugs or worms are included. In Indonesia, the exact number of skin infection incidents has not been established. And until now, there are no research reports about the case pattern of skin infections in the area of Kabupaten Gunung Kidul in 2016. Objective: This research aimed to describe the overview of skin infection cases in Outpatient Dermatology Clinic of RSUD Wonosari, Gunung Kidul fromJanuary 2016 until September 2016. Methods: This research was conducted retrospectively based on medical records of all cases of skin infections in Outpatient Dermatology Clinic of RSUD Wonosari during the period of January 2016 - September 2016. Results: All new cases of skin infections in outpatient dermatology clinic of RSUD Wonosari within the period of January 2016 - September 2016 amounted to 303 cases. The cases consisted of 127 cases of fungal infection (42%) with a variety of cases of dermatophytosis, PVC, and candidiasis; 55 cases of bacterial infections (18%) with a variety of cases of impetigo, folliculitis, leprosy, ektima, erysipelas, furuncles, and abscesses; 40 cases of viral infections (13%) with variaty of cases of HFMD cases, Moluscum contagiosum, zooster, warts, varicella; and 81 cases of parasitic infections (27%) with a variety of cases of scabies, creeping eruption, and pediculosis capitis. Conclusion: Skin diseases caused by infections was still a dominant skin disease in the outpatient Dermatology clinic of RSUD Wonosari, with the number of cases 18.35% of all cases of skin and venereal diseases. The most common cause is infection by fungi (7.69%), followed by parasitic infections, scabies (4.91%), bacterial infections (3.33%), and viral infections (2.42%).